2009
DOI: 10.1111/j.1523-5378.2009.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of IgG Antibody Titer against Helicobacter pylori

Abstract: Combination assay with Hp-IgG titer and pepsinogens may help identify groups at high risk for gastric cancer. Subjects with low Hp-IgG titer and mucosal atrophy were at extremely high risk for gastric cancer, particularly differentiated cancer. Subjects with this background may require ongoing observation and periodic endoscopic examination for early cancer detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 28 publications
7
41
0
1
Order By: Relevance
“…As shown in Table 2, a ''low risk'' stomach reflects less mucosal inflammation and atrophy with preserved acid secretion, which is in line with previous results, indicating that ''low risk'' stomachs according to our criteria have a low likelihood of future cancer development [13,14,16,17,25]. The low incidence of gastric cancer in persons with ''low risk'' stomachs has also been widely reported from Japan as well as other Asian countries, including Korea and China [13,14,16,17,[24][25][26]. Conversely, in terms of the incidence of ''low risk'' stomach among gastric cancer subjects, only 1% to 2% of gastric cancer patients (including cases of noncardia and cardia gastric cancer) showed lack of infection with H. pylori and normal pepsinogen-I levels [27].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As shown in Table 2, a ''low risk'' stomach reflects less mucosal inflammation and atrophy with preserved acid secretion, which is in line with previous results, indicating that ''low risk'' stomachs according to our criteria have a low likelihood of future cancer development [13,14,16,17,25]. The low incidence of gastric cancer in persons with ''low risk'' stomachs has also been widely reported from Japan as well as other Asian countries, including Korea and China [13,14,16,17,[24][25][26]. Conversely, in terms of the incidence of ''low risk'' stomach among gastric cancer subjects, only 1% to 2% of gastric cancer patients (including cases of noncardia and cardia gastric cancer) showed lack of infection with H. pylori and normal pepsinogen-I levels [27].…”
Section: Discussionsupporting
confidence: 88%
“…Ohata [17] reported that no cancer developed in subjects with negative H. pylori infection and normal pepsinogen status during a follow-up of 4655 patients for a period of 7.7 years, and several other investigators [13,14,16] also reported an extremely low incidence of gastric cancer in subjects without gastric mucosal atrophy and inflammation. However, it is important to evaluate atrophy using only objective endoscopic findings during routine endoscopy.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Subjects with an antibody concentration <10 U/mL were classified into the infection-negative group according to the manufacturer's recommended cutoff value; this cutoff value has been widely used in previous studies [6,7,8,11,23,24]. Using these criteria, subjects with a normal PG test and negative status for H. pylori antibody titer were classified into Group A [6,7,8,11].…”
Section: Methodsmentioning
confidence: 99%